The Effectiveness of Inclined Pile Breakwater on the Transmission Coefficient - Lukman Nurzaman; Pitojo Tri Juwono; Very Dermawan; Indradi Wijatmiko (Civil Engineering Journal, 2024)
A breakwater is a structure designed to protect coastal areas by breaking and reducing the force of incoming waves. Waves that propagate through a wave dampening building will have some of their energy reflected (reflection), some of their energy transmitted (transmission), and some of their energy destroyed (dissipation). The effectiveness of wave-breaking structures in protecting coastal and harbor waters can be seen from how much wave energy the building can reduce. In this research, the performance of the wave breaker will be seen from the values of wave transmission (Kt) and wave reflection (Kr) with an inclined pile building structure. Reflection and transmission analysis of the results of 2D physical model testing of wave breakers with inclined pile structures are needed to optimize their use. Laboratory test results prove that this Inclined Pile Structure breakwater is quite effective in scenarios that have smaller Kt values and larger Kr values. In this experiment, testing was carried out with several parameters, namely the slope of the pile, the distance between the piles in one row (or distance between pillars), the distance between the tops of the piles (or distance between rows of piles), and the depth of the water. The Kt value in the model α=45°; D=1.69 cm; b=5 cm is 0.603 compared to the model α=60°; D=1.69cm; b=5 cm, Kt value is 0.652. This shows that the inclined pile structure of breakwater is more effective with a pile slope of 45° than with a pile slope of 60°. Doi: 10.28991/CEJ-2024-010-06-09 Full Text: PDF